Acridine-2, 4-Dinitrophenyl Hydrazone Conjugated Silver Nanoparticles as an Efficient Sensor for Quantification of Mercury in Tap Water. (26th March 2022) - Ali, Imdad; Isaac, Ibanga Okon; Ahmed, Mahmood; Ahmed, Farid; Ikram, Farhat; Ateeq, Muhammad; Alharthy, Rima D.; Malik, Muhammad Imran; Hameed, Abdul; Shah, Muhammad Raza
Abstract : Excretion of heavy metals especially mercury (Hg 2+) from the industries into the environment becomes a major global problem. In this context, mercury is a highly dangerous metal which poses serious impact on human health. In the present study, acridine- (ACR-) based silver nanoparticles (ACR-AgNPs) were prepared and employed as a nanosensor for effective detection and quantification of Hg 2+ in tap water. Conjugation between ACR-based coating agent and silver was examined by UV-visible and FT-IR spectroscopy, while morphology and particle size were determined through atomic force microscopy (AFM), dynamic light scattering (DLS), and scanning electron microscopy (SEM). Furthermore, sensing behavior of nanosensor for metal ions was evaluated by mixing different metals such as Mn 2+, Ni 2+, Ba 2+, Mg 2+, Cr 3+, Pb 2+, Pd 2+, Al 3+, Sn 2+, Fe 2+, Co 2+, Cu 2+, Fe 3+, Cd 2+, and Hg 2+ with ACR-AgNPs. Among all the added metal ions, only Hg 2+ resulted in significant quenching in the absorption intensity of ACR-AgNPs. The limit of detection of the ACR-AgNP-based nanosensor was found to be 1.65 μ M in a wide pH range (1-14). The proposed mercury sensor worked efficiently in the presence of other interfering agents such as other metal ions. Therefore, the synthesized ACR-AgNPs have proved to be an efficient and robust nanosensor for quantitative detection of Hg 2+ in real sample analysis such as tap water. The proposed method does not require expensive instrumentation and trained manpower.